A novel anti-c-Kit antibody–drug conjugate to treat wild-type and activating-mutant c-Kit-positive tumors - Kim, Jin Ock; Kim, Kwang Hyeok; Baek, Eun Ji; Park, Bomi; So, Min Kyung; Ko, Byoung Joon; Ko, Han Jik; Park, Sang Gyu (Molecular Oncology, 2022)
c-Kit overexpression and activating mutations, which are reported in various cancers, including gastrointestinal stromal tumor (GIST), small-cell lung cancer (SCLC), acute myeloid leukemia, acral melanoma, and systemic mastocytosis (SM), confer resistance to tyrosine kinase inhibitors (TKIs). To overcome TKI resistance, an anti-c-Kit antibody–drug conjugate was developed in this study to treat wild-type and mutant c-Kit-positive cancers. NN2101, a fully human IgG1, was conjugated to DM1, a microtubule inhibitor, through N-succinimidyl-4-(N-maleimidomethyl) cyclohexane-1-carboxylate (SMCC) (to give NN2101-DM1). The antitumor activity of NN2101-DM1 was evaluated in vitro and in vivo using various cancer cell lines. NN2101-DM1 exhibited potent growth-inhibitory activities against c-Kit-positive cancer cell lines. In a mouse xenograft model, NN2101-DM1 exhibited potent growth-inhibitory activities against imatinib-resistant GIST and SM cells. In addition, NN2101-DM1 exhibited a significantly higher anti-cancer effect than carboplatin/etoposide against SCLC cells where c-Kit does not mediate cancer pathogenesis. Furthermore, the combination of NN2101-DM1 with imatinib in imatinib-sensitive GIST cells induced complete remission compared with treatment with NN2101-DM1 or imatinib alone in mouse xenograft models. These results suggest that NN2101-DM1 is a potential therapeutic agent for wild-type and mutant c-Kit-positive cancers.
Keywords: Animals; Cell Line, Tumor; Cell Proliferation; Drug Resistance, Neoplasm; Gastrointestinal Stromal Tumors; Humans; Imatinib Mesylate; Immunoconjugates; Lung Neoplasms; Mice; Mutation; Protein Kinase Inhibitors; Proto-Oncogene Proteins c-kit; Receptor Protein-Tyrosine Kinases; Small Cell Lung Carcinoma; antibody-drug conjugate; c-Kit; imatinib-resistant cancer; stem cell factor; tyrosine kinase inhibitor